2019
DOI: 10.1096/fj.201900903rrr
|View full text |Cite
|
Sign up to set email alerts
|

Rutaecarpine derivative R3 attenuates atherosclerosis via inhibiting NLRP3 inflammasome‐related inflammation and modulating cholesterol transport

Abstract: Atherosclerosis is a chronic disease characterized by lipid deposition and inflammatory response. NOD‐, LRR‐ and pyrin domain‐containing protein 3 (NLRP3) inflammasome‐facilitated inflammatory responses are crucial in the pathogenesis of atherosclerosis, and thus new therapeutic approaches are emerging that target NLRP3 and inflammation. Here, we explored the anti‐atherosclerotic effect and mechanisms of a new rutaecarpine derivative, 5‐deoxy‐rutaecarpine (R3) in vitro and in vivo. R3 treatment attenuated athe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 51 publications
2
15
0
Order By: Relevance
“…It is undoubtedly an efficacious strategy for the treatment of GU to ameliorate the aberration of these inflammatory pathological factors. In fact, RUT has pronounced anti-inflammatory capabilities in a variety of disease models according to the reports (Li et al, 2019a;Li et al, 2019b;Luo et al, 2020), which also corroborates our results from the side.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It is undoubtedly an efficacious strategy for the treatment of GU to ameliorate the aberration of these inflammatory pathological factors. In fact, RUT has pronounced anti-inflammatory capabilities in a variety of disease models according to the reports (Li et al, 2019a;Li et al, 2019b;Luo et al, 2020), which also corroborates our results from the side.…”
Section: Discussionsupporting
confidence: 92%
“…However, the mechanism of ethanol damage to gastric mucosa is not completely clear. Previous studies have shown that it is related to the direct damage of gastric epithelial cells (Zhao et al, 2009) and mucus layer (da Silva et al, 2018), or the indirect damage such as the influence of gastric mucosal hemodynamics (Kawano and Tsuji, 2020), infiltration of leukocytes and ensued inflammatory (Li et al, 2017) and oxidative stress (Loguercio et al, 2009;Salaspuro, 2011) and apoptosis distortion (Arab et al, 2019). Thus, this present study focused on the forthputting of RUT to treat ethanol-induced gastric injury through antiinflammatory, anti-oxidation and anti-apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, J774A.1 cells have been used by Yaron and collaborators to demonstrate that K + efflux is upstream of Ca 2+ influx in the production of mtROS, thus beginning the cascade of events leading to NLRP3 inflammasome activation [ 75 ]. J774A.1 cells have been widely used to test the efficacy of potentially novel inhibitors of NLRP3 [ 53 , 76 , 77 , 78 ]. For instance, Hu et al nicely demonstrated that the antimicrobial cathelicidin peptide LL-37 inhibits LPS/ATP-mediated pyroptosis, thus providing new insights into modulation of sepsis [ 79 ].…”
Section: Cell Models To Study Nlrp3 Inflammasome Biologymentioning
confidence: 99%
“…It potentially inhibits the production of inflammatory mediators by macrophages and lymphocytes [ 25 ]. Inhibition of NF- κ B and mitogen-activated protein kinase (MAPK) pathways in rutaecarpine-derivative R3 inhibits the NLRP3 inflammasome activation, which consequently lowers the expression of proinflammatory cytokine IL-1 β [ 26 , 27 ]. The pathogenesis of GA is highly associated with the inflammatory cascade induced by the activation of the inflammatory bodies of NLRP3 [ 2 ].…”
Section: Discussionmentioning
confidence: 99%